Pengaruh Program Latihan Interval Intensitas Tinggi dalam Meningkatkan Kapasitas VO2maks dan Pemulihan Denyut Jantung - Permana, Dwinda Abi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aimed to examine the effect of a High Intensity Interval Training (HIIT) program on VO2max capacity and heart rate recovery. Thirteen student athletes participated in the study: male, biological age 15-17 years, training age >5 years, and completed multilateral training. An experimental method with a one-group pretest-posttest design was used for four weeks. Data were collected before and after each training session using the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) procedure and heart rate recovery monitoring with a Polar-H10 heart rate monitor in a HIIT protocol with a work:rest ratio (1:1). Data from all subjects were processed using SPSS software, and then hypothesis testing was conducted using a pre-test. The results showed a significant increase (p<0.05) in VO2max capacity (2.8±1.4 ml/kg-1.min-1) and heart rate recovery (9.9±9.2). With the increase in VO2max accompanied by heart rate recovery, it can be concluded that the HIIT program has been proven effective in improving aerobic capacity and accelerating the recovery process, thus supporting more optimal athlete performance.